Terorisme tinjauan psiko-politis, peran media, kemiskinan, dan keamanan nasional - Djelantik, Sukawarsini (Yayasan Pustaka Obor Indonesia, 2010)
Study on terrorism from psychology, politics, media role, economic, and national security viewpoints.